2017
DOI: 10.3126/jpan.v4i1.16743
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude of women towards alcohol use and related problems in the Eastern part of Nepal

Abstract: Introduction: Exploring the levels of knowledge and attitude of women towards alcohol use and related problems will enable a more efficient process of awareness creation and it will allow the program to be tailored more appropriately to the needs of the community. Females with alcohol problems are severely impaired; have adverse consequences and more alcohol related physical, psychological and social harm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…But the study showed in Nepal, the knowledge about alcohol use during pregnancy was inadequate. Only 26.5% had an adequate knowledge and 23.93% had a positive attitude towards alcohol consumption [20].This difference might be due to educational level and their culture that has been experienced in the study area. The ndings supplement that, one in ve women have a neutral or positive attitude towards alcohol consumption in pregnancy.…”
Section: Discussionmentioning
confidence: 85%
“…But the study showed in Nepal, the knowledge about alcohol use during pregnancy was inadequate. Only 26.5% had an adequate knowledge and 23.93% had a positive attitude towards alcohol consumption [20].This difference might be due to educational level and their culture that has been experienced in the study area. The ndings supplement that, one in ve women have a neutral or positive attitude towards alcohol consumption in pregnancy.…”
Section: Discussionmentioning
confidence: 85%
“…In Nepal, the knowledge about alcohol use during pregnancy was inadequate. Only 26.5% had adequate knowledge and 23.93% had positive attitude towards alcohol consumption [8] . Tribal women and family members perceive alcohol as a part of their routine lives and therefore continue consuming alcohol during pregnancy.…”
Section: Introductionmentioning
confidence: 96%